Can AI Predict Rehabilitation Outcomes? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2021)
Artificial intelligence (AI) is no longer a futuristic concept but a present-day reality that is reshaping numerous industries, including healthcare. Within ...
Keywords: AI in Rehabilitation Medicine; Predict; Rehabilitation; Outcomes; Artificial Intelligence; Machine Learning; Deep Learning